2006
DOI: 10.1002/masy.200690062
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Cavitation in HDPE Using Time Resolved Synchrotron X‐ray Scattering During Tensile Deformation

Abstract: Real time synchrotron Small‐Angle and Wide‐Angle X‐ray Scattering was performed during the tensile deformation of a high‐density polyethylene copolymer. The changes of the structure in the crystalline and in the amorphous domains were followed during the three characteristic stages of the load‐displacement curves: The elastic stage and the plastic range composed of the stage of the lowering load in the force‐displacement‐curve (yielding) and the strain hardening. Competitive phenomena like crystallite fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 15 publications
4
60
0
Order By: Relevance
“…The cavitation in tensile drawing of high density polyethylene was studied by Butler et al [3,6], Addiego et al [13], Schneider et al [14] and others. Butler et al [15] examined in-situ small-and wide-angle X-ray scattering from deformed quenched and annealed PE samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cavitation in tensile drawing of high density polyethylene was studied by Butler et al [3,6], Addiego et al [13], Schneider et al [14] and others. Butler et al [15] examined in-situ small-and wide-angle X-ray scattering from deformed quenched and annealed PE samples.…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron radiation also was used by Schneider et al [14] for the studies of HDPE deformation. They concluded that a competitive phenomena like crystallite fragmentation and cavitation occur simultaneously at yielding.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation behavior has been found in many semi-crystalline polymers, including isotacticpolypropylene (iPP) [1,2], polyethylene (PE) [3,4], poly(1-butene) (P1B) [5], and so on, when these polymers are stretched above their glass transition temperature. Stress whitening can be regarded as the scattering of visible light by voids detected by naked eye.…”
Section: Cavitation Behavior Of Semi-crystalline Polymersmentioning
confidence: 99%
“…The first synchrotron light source was the Stanford Synchrotron Radiation Laboratory (SSRL) build in 1977 [28]. Nowadays, a few synchrotron radiations have been set up all over the world, and the synchrotron radiation has been developed into the third generation, to name a few, European Synchrotron Radiation Facility (ESRF) in France [3], Deutsches Elektronen-Synchrotron (DESY) in Germany (see Figure 2) [29], Shanghai Synchrotron Radiation Facility (SSRF) [30] in China, and so on. At PETRA III of DESY, the size of the X-ray beam could reach a few micrometers and the exposure time could be milliseconds.…”
Section: Role Of the State Of Amorphous Phasementioning
confidence: 99%
“…Figure 5a and Figure 5b show examples of the equatorial and the meridional SAXS intensity profiles, I EQ q 2 and I MR q 2 respectively, recorded during the tensile deformation between the yield point and the start of strain hardening [Y-S] with strain in the range e 2 [0.05-3.0]. [6] The evolution of the first peak of the crystallites at q % 0.22 nm À1 can be followed. The second correlation peak is less pronounced in comparison with first peak; the short exposure time does not allow both peaks to be recorded with reasonable statistics.…”
Section: Waxs/saxs During Tensile Deformation Of Polyethylene (Pe)mentioning
confidence: 99%